Chronic idiopathic angioedema: a single center experience - Eli, Magen; Joseph, Mishal; Kuznik, Boris; Menachem, Schlesinger (International journal of dermatology, 2014)
Objective Chronic idiopathic angioedema (CIA) is defined as three or more episodes of angioedema in a period of > 6 months without a clear etiology. In the study, we tried to explore clinical and laboratory characteristics of patients with CIA unaccompanied by urticaria. Methods We retrospectively reviewed clinical and laboratory characteristics of 1238 patients with chronic urticaria and/or angioedema referred to our allergy clinic. Results Eight hundred and forty‐one (67.9%) subjects had chronic urticaria without angioedema (CU Group), 323 (26.1%) had both urticaria and angioedema (CU + CA group), and 74 (5.9%) had chronic angioedema without urticaria (CA). In 29 (39.2%) cases of CA, no etiologic factor of angioedema was discovered, thus the patients were defined as having chronic idiopathic angioedema (CIA Group). Twenty‐two (75.8%) subjects had antihistamine‐responsive CIA and seven (24.1%) had antihistamine‐unresponsive CIA. There were no statistically significant differences in clinical (except of urticarial eruptions) and laboratory characteristics between CU, CA + CU, and CIA groups. Antihistamine responsive and antihistamine‐unresponsive CIA groups had no distinguishable clinical or laboratory features. Conclusions We suppose that CIA, at least its antihistamine‐responsive form, represents a rare form of chronic spontaneous urticaria. The reasons why in CIA there are no other clinical signs of mast cell/basophil activation, such as pruritus, urticarial, and dermatographism, are largely unknown and have to be elucidated in future studies.